Specifics of Phase Formation in Refractory Clay in the Presence of Topaz - Vakalova T. V. Tatyana Viktorovna; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Chernousova O. A.; Khabas (Habas) T. A. Tamara Andreevna; Golovanov V. M. (2001, 2001)
The processes of phase formation in refractory clay in the presence of topaz-bearing rock additives are investigated. It is established that the effect of topaz proper is determined by its quantity. Topaz in low quantities (up to 0.5 - 1.0 %) intensifies the formation of primary and secondary mullite of prismatic habitus, lowers the temperature of mullite synthesis, and improves the mullite structure. An increase in the topaz content over 25 % is accompanied by the formation of mullite of needle-shaped habitus, in addition to prismatic mullite